Constraints on Early Star Formation and Mixing from Nucleosynthesis in Protogalactic clouds - Lan, Nguyen Quynh; Giang, Nguyen Thu; Mathews, Grant J; Saleh, Lamya (Communications in Physics, 2012)
We calculate the stochastic chemical evolution of pre-galactic clouds as a means to constrain the degree of mixing in the early Galaxy. We employ a model based upon the cold-dark-matter paradigm for hierarchical galaxy formation. We argue that a significant dispersion in the metallicity for the alpha elements as a function of heavy elements is unavoidable for models with realistic stellar nucleosynthesis yields and a reasonable initial mass function. Although the calculated scatter in light-element abundance can be reduced by restricting the stellar initial mass function. The observed lack of dispersion requires inevitably requires that extensive mixing of the supernova eject containing alpha elements to have occurred. We use the difference between the observed and calculated dispersion of alpha to determine the degree of mixing of the early Galaxy. We argue that the large dispersion for heavy r-process elements suggests that they arise from rare events which did not have time to mix during the formation of the Galactic halo.